Simpler UNBab Mapping Function For Global Positioning System (GPS) Thopospheric Delay - Sakidin, Hamzah; Tay, Choo Chuan (2009)
The UNBab(E)mapping function models should be simplified 10 allow fatter calculation and also better undemanding of the models. Many modern mapping function models use mapping functions in the form of continued fractions which is quite tedious in calculation. There are 7 mathematical operations for tWSoi(£)'o he carried out before getting the mapping function scale factor. The mapping functions for tWfloft(£) models for hydrostatic and non hydrostatic components are given in a form of continued fraction arc to be simplified, due to its ability to calculate mapping function value down to 2 degree of elevation angle. By using linear, hyperbolic, logarithm and also regression method, the mapping function models can be simplified and at the same lime can produce the same result. The calculation of sum of errors shows that the deviation of the simplified models from the original models is not significant. As a coefficient of zenith hydrostatic delay and also zenith non hydrostatic delay, the mapping function scale factor value plays an important role for getting the total tropospheric delay value. So. this value will give minimum value for the tropospheric delay (TD).